Chemometric determination of naproxen sodium and pseudoephedrine hydrochloride in tablets by HPLC - (:unkn) unknown (PHARMACEUTICAL SOC JAPAN, 2006)
A new chemometric determination by high-performance liquid chromatography (HPLC) with photodiode array (PDA) detection was implemented for the simultaneous determination of naproxen sodium and pseudoephedrine hydrochloride in tablets. Three chemometric calibration techniques, classical least squares (CLS), principle component regression (PCR) and partial least squares (PLS) were applied to the peak area at multiwavelength PDA detector responses. The combinations of HPLC with chernometric calibration techniques were called HPLC-CLS, HPLC-PCR and HPLC-PLS. For comparison purposes the HPLC method called the classic HPLC method was used to confirm the results obtained from combined HPLC-chemometric calibration techniques. A good chromatographic separation between two drugs with losartan potassium as an internal standard was achieved using a Waters Symmetry (R) C18 Column 5 mu m 4.6 +/- 250 mm and a mobile phase containing 0.2 m acetate buffer and acetonitrile (v/v, 40 : 60). The multiwavelength PDA detection was measured at five different wavelengths. The chromatograms were recorded as a training set in the mobile phase. Three HPLC-chemometric calibrations and the classic-HPLC method were used to test the synthetic mixtures of naproxen sodium and pseudoephedrine hydrochloride in the presence of the internal standard. The HPLC-chemometric approaches were applied to real samples containing drugs of interest. The experimental results obtained from HPLC-chemometric calibrations were compared with those obtained by a classic HPLC method.
Keywords: HPLC-chemometric calibration; quantitative determination; naproxen sodium; pseudoephedrine hydrochloride; pharmaceutical preparation; SPECTRA DERIVATIVE SPECTROPHOTOMETRY; PERFORMANCE LIQUID-CHROMATOGRAPHY; MULTIVARIATE CALIBRATION; PHARMACEUTICAL FORMULATIONS; LEAST-SQUARES; QUANTITATIVE-ANALYSIS; IBUPROFEN